The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1159/000332829
|View full text |Cite
|
Sign up to set email alerts
|

Acute Pharmacokinetics of Memantine in the Mouse

Abstract: The pharmacokinetics of memantine, a widely prescribed medication in the United States and the European Union for the treatment of moderate-to-severe Alzheimer’s disease (AD), have not been well explored in the mouse. Memantine is a highly unspecific blocker of many channels and how memantine may be of benefit in AD remains a mystery. Therefore, the investigation of memantine in the mouse, the most commonly chosen subject for modeling AD, has strong potential to lead to better therapies. Here, we present an ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 39 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…injections of 5 mg/kg memantine selectively enhanced the behavioural performance of Ts65Dn mice in a fear conditioning test. Similar to previously published work in which memantine was injected subcutaneously (s.c.) in wild‐type mice , concentrations of memantine in plasma, brain and liver displayed a dose‐dependent linear growth (fig. ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…injections of 5 mg/kg memantine selectively enhanced the behavioural performance of Ts65Dn mice in a fear conditioning test. Similar to previously published work in which memantine was injected subcutaneously (s.c.) in wild‐type mice , concentrations of memantine in plasma, brain and liver displayed a dose‐dependent linear growth (fig. ).…”
Section: Resultsmentioning
confidence: 99%
“…We have shown that the memantine distribution in plasma, brain and liver of Ts65Dn and euploid F1 hybrid mice in response to single i.p., acute administrations of increasing doses of this drug (2.5–40 mg/kg) follows a simple linear dose dependence. This is in agreement with previously reported work in which memantine was injected s.c. to wild‐type C57CL/6 mice . In that study, these authors observed that 10 mg/kg memantine s.c. produced a mean plasma concentration of 2.15 μmol/l 100 min.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rather, these data strongly suggest that memantine causes lasting alterations in glutamatergic synaptic transmission in the ventral hippocampus. In vivo, memantine remains in plasma for up to 132 h after oral administration [28] and can be detected in mouse brain 100 min after administration [29]. According to microdialysis data, the half-life of memantine in rodent brain is approximately 3 h [30].…”
Section: Ca1mentioning
confidence: 99%